Electron tomography of whole cultured cells using novel transmission electron imaging technique. (January 2018) - Okumura, Taiga; Shoji, Minami; Hisada, Akiko; Ominami, Yusuke; Ito, Sukehiro; Ushiki, Tatsuo; Nakajima, Masato; Ohshima, Takashi
Highlights: Plate-TEM tomography was developed for 3D observation of cellular structures. The structures can be observed at high resolution, as cells remain on a plate. Both surface and internal structures can be observed simultaneously. Light microscopy is possible for Plate-TEM samples since the plate is transparent. Correlative observation is possible because Plate-TEM is not destructive. Abstract: Since a three-dimensional (3D) cellular ultrastructure is significant for biological functions, it has been investigated using various electron microscopic techniques. Although transmission electron microscopy (TEM)-based techniques are traditionally used, cells must be embedded in resin and sliced into ultrathin sections in sample preparation processes. Block-face observation using a scanning electron microscope (SEM) has also been recently applied to 3D observation of cellular components, but this is a destructive inspection and does not allow re-examination. Therefore, we developed electron tomography using a transmission electron imaging technique called Plate-TEM. With Plate-TEM, the cells cultured directly on a scintillator plate are inserted into a conventional SEM equipped with a Plate-TEM observation system, and their internal structures are observed by detecting scintillation light produced by electrons passing through the cells. This technology has the following four advantages. First, the cells cultured on the plate can be observed at electron-microscopic resolution since they remain on the plate. Second, both surface and internal information can be obtained simultaneously by using electron- and photo-detectors, respectively, because a Plate-TEM detector is installed in an SEM. Third, the cells on the scintillator plate can also be inspected using light microscopy because the plate has transparent features. Finally, correlative observation with other techniques, such as conventional TEM, is possible after Plate-TEM observation because Plate-TEM is a non-destructive analysis technique. We also designed a sample stage to tilt the samples for tomography with Plate-TEM, by which 3D organization of cellular structures can be visualized as a whole cell. In the present study, Mm2T cells were investigated using our tomography system, resulting in 3D visualization of cell organelles such as mitochondria, lipid droplets, and microvilli. Correlative observations with various imaging techniques were also conducted by successive observations with light microscopy, SEM, Plate-TEM, and conventional TEM. Consequently, the Plate-TEM tomography technique encourages understanding of cellular structures at high resolution, which can contribute to cellular biological research.